2019
DOI: 10.2217/bmm-2019-0098
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Mir-21, Mir-146B and Mir-326 As Potential Biomarkers in Behcet'S Disease

Abstract: Aim: Behcet's disease (BD) is a vasculitis. Lines of evidence suggest miRNAs as diagnostic and prognostic markers in autoimmune diseases. This study was designed to investigate the potential role of miR-21, miR-146b and miR-326 as biomarkers for diagnosis, predicting organs involvement and measuring BD activity. Patients & methods: In this cross-sectional study, the study groups consisted of 46 BD patients and 70 age- and sex-matched healthy volunteers. The expression rates of three miRNAs were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“… 26 For example, miR-326 expression could be used as a potential biomarker in patients with Behcet's disease. 27 Serum miR-21 and miR-221 were used as biomarkers for cerebrovascular diseases. 28 Besides, miR-30-5p might be a clinical biomarker for AS.…”
Section: Discussionmentioning
confidence: 99%
“… 26 For example, miR-326 expression could be used as a potential biomarker in patients with Behcet's disease. 27 Serum miR-21 and miR-221 were used as biomarkers for cerebrovascular diseases. 28 Besides, miR-30-5p might be a clinical biomarker for AS.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently verified the expression levels of a set of selected candidate miRNAs that are related to allergic and autoimmune diseases, such as upregulated miRNAs (miR-326, miR-142-5p) and downregulated miRNAs (miR-644a, miR-181a2-3p) [ 31 , 32 , 33 ], by qRT-PCR in LS tissues from the same patients examined by RNASeq ( Figure 2 A) and from an additional cohort of LS patients by qRT-PCR. Our data showed that the upregulated miRNAs, miR-326, miR-142-5p and downregulated miRNAs, miR-644a, miR-181a-2-3p were concordant with our RNASeq data ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Jadideslam and colleagues compared the expression of miR-21, miR-146b, and miR-326 in PBMCs from Iranian Azari BD patients with that in healthy controls, and revealed the downregulation of miR-21 and upregulation of miR-326. Furthermore, they suggested the great potential of miR-326 as a biomarker for predicting the uveitis and severe eye involvement in BD (Jadideslam et al, 2019).…”
Section: Micrornas and Behcet's Diseasementioning
confidence: 99%